ANALISIS IMPLEMENTASI PROSEDUR PENANGANAN DAN SARANA PENYELAMATAN DALAM MENGHADAPI KEADAAN DARURAT KEBAKARAN DI MALL X SEMARANG - Angel Rumiris Sabathini Tampubolon; Bina Kurniawan; Daru Lestantyo (Jurnal Kesehatan Masyarakat (Undip), 2018)
The shopping center is  type of high-rise building which is a public facility with the number of non-permanent residents from various groups, having different knowledge about self-rescue efforts during emergencies. Handling procedures and means of rescue during an emergency need to be owned by the management to facilitate the evacuation process. The purpose of this study was to analyze the implementation of handling procedures and rescue facilities during emergencies at Mall X Semarang. This research is a type of qualitative research with methods of observation and in-depth interviews. Using two types of informants namely primary and triangulation as data validity. The results showed that the fire management managed by the manager of Mall X had been planned and implemented quite well, as evidenced by the establishment of emergency response organizations with trained resources, there were procedures for handling emergencies and regular training. Whereas for the completeness of the rescue facilities some aspects have not met the standards of SNI namely the existence of direction markers that have not been equipped in all areas of the mall until it comes out to gathering point, emergency lights that have not been installed on all emergency stairs. The completeness of the rescue facilities needs to be reviewed and made improvements to the facilities that have been damaged. From this study it can be concluded that the procedures for handling and rescue facilities in Mall X have not been so good because they still have to complete several components requested by the applicable standards.